Report of the International Court of Justice - United Nations Department for General Assembly; Conference Management (United Nations, 2016)
This report is about the work of the International Court of Justice. It presents the Court’s jurisdiction, its functions, the publications and documents produced and the website managed, its finances, and the status of the pending contentious, as well as advisory proceedings during the period under review.